2011
DOI: 10.1007/s10120-011-0105-6
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of micrometastasis by sentinel node navigation surgery using indocyanine green and infrared ray laparoscopy system for gastric cancer

Abstract: Since all 27 lymph nodes in 15 patients with metastasis by IHC staining but not by HE staining were micrometastasis or less and included in the SN, ICG-positive lymphatic basin dissection by SNNS with infrared ray observation seems to be an adequate method of lymph node dissection for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…In recent years, computed tomography lymphangiography, infrared ray electronic endoscopy, and indocyanine green fluorescence imaging are emerging as new tracers for laparoscopic SN biopsy [71,[80][81][82][83][84] .…”
Section: Laparoscopic Function-preserving Surgerymentioning
confidence: 99%
“…In recent years, computed tomography lymphangiography, infrared ray electronic endoscopy, and indocyanine green fluorescence imaging are emerging as new tracers for laparoscopic SN biopsy [71,[80][81][82][83][84] .…”
Section: Laparoscopic Function-preserving Surgerymentioning
confidence: 99%
“…Among NIR fluorophores, the most used is indocyanine green (ICG), that in addition to its NIR fluorescent emission, it is the only dye that has been approved by the United States Food and Drug Administration for noninvasive NIR-fluorescence imaging for clinical application (to determine blood flow, to perform ophthalmic angiography, and to evaluate sentinel lymph nodes [3132]). In order to study by FLI the expression of folate receptor (and as a consequence, the proliferation process), FA was conjugated with ICG in different designs [3334].…”
Section: Molecular Processesmentioning
confidence: 99%
“…7 which is defined as LNs along the trunk of left gastric artery between its root and the origin of its ascending branch by Japanese Gastric Cancer Association. Yano et al[34] investigated 130 patients with gastric cancer (3381 LNs) who underwent SNNS by IREE with ICG injection and evaluated LNs by immunohistochemistry (IH) with anti-cytokeratin antibody staining. They reported that 15 patients (27 nodes) were diagnosed without metastasis by hematoxylin and eosin (HE) staining, which turned to metastatic by IH staining.…”
Section: Snns As a Solution To Predict Ln Metastasis Of Egcmentioning
confidence: 99%